Laser processing of continuous carbon fibre reinforced polyphenylene sulphide organic sheets—Correlation of process parameters and reduction in static tensile strength properties. (March 2014) - Jaeschke, Peter; Kern, Manuel; Stute, Uwe; Kracht, Dietmar; Haferkamp, Heinz
In this article, the impact of laser-induced thermal damage on the static strength properties of consolidated continuous carbon fibre reinforced thermoplastics induced by high-power laser cutting is presented. Organic sheets based on a polyphenylene sulphide matrix are machined using a fibre laser providing a maximum output power of 6000 W. In this context, the influence of the applied laser power and the feed rate on the cut quality as well as the resulting tensile strength is discussed. In order to analyse the laser cutting edge through a quantitative evaluation of the damaged areas due to laser impact, optical micrographs are prepared. The results of tensile strength tests are compared with those measured from the specimens that were generated by a conventional processing technique (milling). A linear dependency between a specific part of the heat-influenced zone and the corresponding maximum tensile load is found. A reduced load bearing area, as a consequence of a modified fibre–matrix-structure due to laser impact, is identified as the responsible factor for reduced tensile strengths, especially for low feed rates.